New horizons in the sociology of sport - Giulianotti, Richard; Thiel, Ansgar (Frontiers in Sports and Active Living, 2023)
The relevance of a sociological view on the problems of society has never been as important as it is today. To quote the editors of the journal Nature in their editorial, Time for the Social Sciences, from 2015: if you want science to deliver for society, you need to support a capacity to understand that society. In other words, the technological and scientific disciplines cannot simply transfer their findings into everyday life without knowing how society works. But this realisation does not seem to have caught on everywhere. The sociology of sport is entering a critical period that will shape its development and potential transformation over the next decade. In this paper, we review key features and trends within the sociology of sport in recent times, and set out potential future challenges and ways forward for the subdiscipline. Accordingly, our discussion spans a wide range of issues concerning the sociology of sport, including theories and approaches, methods, and substantive research topics. We also discuss the potential contributions of the sociology of sport to addressing key societal challenges. To examine these issues, the paper is organized into three main parts. First, we identify three main concentric challenges, or types of peripheral status, that sociologists of sport must confront: as social scientists, as sociologists, and as sociologists of sport, respectively. Second, we consider various strengths within the positions of sociology and the sociology of sport. Third, in some detail, we set out several ways forward for the sociology of sport with respect to positioning within academe, scaling up research, embracing the glocal and cosmopolitan aspects of sociology, enhancing plurality in theory, improving transnational coordination, promoting horizontal collaborations, and building greater public engagement. The paper is underpinned by over 60 years (combined) of work within the sociology of sport, including extensive international research and teaching.